INCREASING STUDENTS VOCABULARY BY USING COMIC STRIPS : A Study Conducted at SMP Anugrah Tondano - Korompot, Rahman; Olii, Sanerita T.; Rorimpandey, Rinny (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2022)
This research aims at finding out whether the use of comic strips could increase the students vocabulary or not In conducting this research quantitative method with pre experimental design one group pre test and post test is used This research is carried out at SMP Anugrah Tondano in which the subject of this research is 8 first grade students of SMP Anugrah Tondano The data are collected through matching test and are analyzed by using the mean score formula The findings show that the mean score of the post test 85 6 is higher than the pre test score 58 1 It indicates that Comic Strips is effective way to increase students vocabulary So it can be concluded that the use of Comic Strips as a technique is effective to increase the students vocabulary Since this study is conducted in the pre experimental design further studies with the experimental design are expected to show the effectiveness of using comic strips in English Language Teaching < p>